Innovativeness and sustainable innovations in social businesses in Lithuania: experiences of women social entrepreneurs - Novelskaitė, Aurelija; Pučėtaitė, Raminta; Pušinaitė-Gelgotė, Rasa (Information & Media, 2018)
This paper focuses on the perceptions of women social entrepreneurs of in the field of innovativeness forms and sustainable innovations. It presents empirical findings derived from interviews (n=18) with women representatives of social businesses in Lithuania. An analysis of the interview materials reveals that women social entrepreneurs define innovativeness on both individual and organizational levels, but the definition of sustainable innovation was related to more global contexts and technological advancement. The findings correspond to the results of previous works in the field. Thus, on the one hand, the findings denote the universality of the topic; on the other hand, this shows the validity of the Lithuanian study.